2011
DOI: 10.1007/s10863-011-9365-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trypanosoma cruzi peroxiredoxins in mitochondrial bioenergetics

Abstract: Trypanosoma cruzi cytosolic (TcCPx) and mitochondrial tryparedoxin peroxidase (TcMPx) play a fundamental role in H(2)O(2) detoxification. Herein, mitochondrial bioenergetics was evaluated in cells that overexpressed TcCPx (CPx) and TcMPx (MPx) and in pTEX. In MPx, a higher expression was observed for TcCPx, and the same correlation was true for CPx. Differences in H(2)O(2) release among the overexpressing cells were detected when the mitochondrial respiratory chain was inhibited using antimycin A or thenoyltri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
1
13
0
3
Order By: Relevance
“…1C). These values are comparable to those from other studies using pTEX or pTEX-derived vectors to overexpress proteins in the cytosol (78,79), mitochondria (80), glycosomes (81), endosomal/lysosomal system and reservosomes (75,82), ER (68), flagellar pocket (83), or plasma membrane (69,(84)(85)(86) of T. cruzi. The protein was stable, with no indication of a C-terminal proteolytic cleavage event observed when expressed in L. tarentolae (21), and it appeared to be inserted into the rER and N-glycosylated normally (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…1C). These values are comparable to those from other studies using pTEX or pTEX-derived vectors to overexpress proteins in the cytosol (78,79), mitochondria (80), glycosomes (81), endosomal/lysosomal system and reservosomes (75,82), ER (68), flagellar pocket (83), or plasma membrane (69,(84)(85)(86) of T. cruzi. The protein was stable, with no indication of a C-terminal proteolytic cleavage event observed when expressed in L. tarentolae (21), and it appeared to be inserted into the rER and N-glycosylated normally (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Although it is difficult to exclude the possibility that the 7-fold overexpression of a single protein, such as TcOGNT2, inhibits metacyclogenesis by a nonspecific stress effect, it is notable that proliferation and TCT production were not affected ( Fig. 8 and 9) and that overexpression of other proteins failed to inhibit this process (58,68,69,(78)(79)(80)(81)(82)(84)(85)(86). The protein burden of 7-fold accumulation of a single enzyme is not anticipated to be great, and indeed, overexpression of a truncated N-terminal fragment of the TcOGNT2 homolog TbOGNT2 in Trypanosoma brucei did not affect Golgi replication (93).…”
Section: Discussionmentioning
confidence: 99%
“…The protein extracts (30 µg) were separated and electroblotted onto a nitrocellulose membrane using the Trans-Blot SD Semi-Dry Electrophoretic Transfer Cell (Bio-Rad, CA, USA). The membranes were blocked by incubation with 5% instant nonfat dried milk in PBS 0.05% Tween 20 (PBS-T) for 1 h, washed and incubated in the presence of polyclonal antibodies raised against T. cruzi TcMPx (1∶2000) and TcCPx (1∶2500) for 2 h. After three 15 min washes with PBS-T, the membranes were incubated with HRP-linked anti-rabbit IgG (Cell Signaling Technology, MA, USA, 1∶5000 dilution) for 1 h at room temperature and washed three times with PBS [22], [37]. Bands were revealed using the Super Signal Detection Kit (Thermo Scientific, Pierce, IL, USA).…”
Section: Methodsmentioning
confidence: 99%
“…cytotoxic oxidants (Piacenza et al, 2008;Arias et al, 2013;Martínez et al, 2019). The expression levels of cTXNPx as well as of mTXNPx are increased in infective and intracellular stages of the parasite (Zago et al, 2016); these two enzymes work in concert to control the cytosolic and mitochondrial oxidative stress (De Figueiredo Peloso et al, 2011), and are extensively studied for the design of anti-parasite therapies. Lastly, annotation of the parasite genome has revealed that T. cruzi lacks catalase, glutathione reductase, thioredoxin reductase, and selenium-dependent glutathione peroxidases (El-Sayed et al, 2005).…”
Section: A Network Of Antioxidant Enzymes In T Cruzimentioning
confidence: 99%